Prevalence of Hyponatremia in Chronic Liver Disease Patients and its Correlation with Disease Severity - Priya, Khushboo; Sah, Dipak Kumar; Thadhiya, Rajan Kumar (Journal of Nepalgunj Medical College, 2025)
Introduction: Hyponatremia is the most common electrolyte abnormality in patients with chronic liver disease, signaling poor prognosis and contributing to mortality worldwide. In CLD, hyponatremia is often linked to more severe liver disease and is an independent predictor of worse outcomes, including complications like difficult-to-control ascites, hepatic encephalopathy, and increased mortality. Aims: To determine the prevalence of hyponatremia in patients with chronic liver disease and its correlation with disease severity. Methods: This descriptive cross-sectional study enrolled 104 patients with chronic liver disease admitted to Nobel Medical College from July 2024 to June 2025. Demographic data, medical history, and risk factors were collected via structured questionnaire. Chronic liver disease severity was assessed using the Child-Pugh scoring system. Data were analyzed with SPSS version 20.0; p < 0.05 indicated statistical significance. Results: Chronic liver disease prevalence was 25.9%, with a mean age of 50.6 years, with male predominance (71.2%). Alcohol was the leading cause (80.8%), followed by metabolic dysfunction-associated steatotic liver disease (13.5%). Common symptoms included ascites (68.2%) and jaundice (58.7%). Major complications were varices (39.4%), portal hypertension (33.7%), and encephalopathy (23.1%). Hyponatremia was observed in 74 (71.2%), and normal sodium in 30 (28.8%). Spearman’s rank correlation analysis showed no significant association between Child-Turcotte-Pugh score and hyponatremia (ρ = –0.068, p = 0.494). Conclusion: The prevalence of hyponatremia among the patients with chronic liver disease was found to be higher and found no correlation between Child-Turcotte-Pugh class and hyponatremia.